Financial ratio to distinguish banks Islamic business units and conventional banks in Indonesia - Ulfi Kartika Oktaviana (Kementerian Agama Republik Indonesia Direktorat Jenderal Pendidikan Islam Direktorat Pendidikan Tinggi Islam, 2012)
har,1/nr,c.1